Integrating interactive, edutainment technology with project-based learning: A pedagogical model for inclusive classrooms / Anuar Mohd Yusof - Anuar , Mohd Yusof (2017)
The current scenario in the inclusive classroom is that the special needs learner is labelled as a learner with low capability and the content and learning environment is designed for prime learners but not for special needs learners. Thus, the special needs learners may not receive the appropriate instruction in the inclusive classroom. Therefore, the present study put forward an alternative pedagogical model that captures special needs learners’ attention as well as supports their ability to collaborate with prime learners in an inclusive classroom. Specifically, three objectives formed the basis of the study namely, (i) To design an eProjBL pedagogical model incorporating interactive edutainment applications for selected primary school learners in an inclusive classroom; (ii) To investigate teachers’ perceptions of the eProjBL pedagogical model in an inclusive classroom, and (iii) To explore the acquiring of the skills in using the eProjBL pedagogical model among the selected primary school learners in an inclusive classroom. The study had four phases. The first preliminary phase reviewed issues related to the challenge of special education through literature and conversations with relevant stakeholders. The second phase of the study focused upon the conceptual design and the theoretical framework together with the content to be utilised through the alternative pedagogical model being proposed. The eProjBl model was based upon the Project Based learning design blended with technology and edutainment applications. The Theoretical Framework leaned heavily upon Lev Vygotsky’s theory and concept of Zone of Proximal Development (ZPD) in game design. The edutainment applications included Augmented Reality, Virtual Game-based, Game–based and Animation components. The samples for the study were selected schools and according to the approached school’s ethical procedures. Data collection techniques included observations, semi-structure interviews, field notes, an engagement survey form and evaluation rubrics. Phase three was the pilot testing stage where the instruments were validated and tested. This was followed by the actual testing in the field. The final fourth phase was the analysis and interpretation stage where the data collected were scrutinised carefully. The strengths of the eProjBl model showed that special needs’ learners were able to visualise the topic being taught better, displayed self-motivation and were able to explore the concept on their own which indirectly enhanced their communication skills. The weaknesses included the time that was taken by the teachers to set up the class. Teachers’ perception of the eProjBL model showed that the flow of the process of the eProjBL pedagogical model was very effective and systematic so as to be able to achieve the lesson objectives. Teachers’ evaluation of four themes showed that the mean values for the prime learners’ performance for Character, Teamwork, Artefact and Presentation were 3.05, 3.08, 2.98 and 2.75 respectively; while the mean values for the special needs learners were 2.43, 2.32, 2.53 and 2.59 respectively. The extent of skills acquired showed that overall the mean value for the prime learners were slightly higher than the special needs learners. The implications of the findings and suggestions for further study is also discussed.